Pharmacotherapy for the peripartum management of bipolar disorder. (22nd September 2019) - Belzeaux, Raoul; Sanguinetti, Catherine; Murru, Andrea; Verdolini, Norma; Pacchiarotti, Isabella; Hidalgo-Mazzei, Diego; Cohen, Lola; Anmella, Gerard; Barbuti, Margherita; Vieta, Eduard; Llorca, Pierre-Michel; Samalin, Ludovic
ABSTRACT: Introduction : The peripartum period in bipolar disorder (BD) patients is associated with high risk of relapse. Relapse during this period may affect fetal and child development. The consequences of psychotropic medication during pregnancy are also a major concern. The extent to which mood stabilizers may potentially affect the embryogenesis or the child development varies from high (e.g. valproate) to less clear and more debated (e.g. lithium). Areas covered : This review describes the current state of evidence with respect to the impact of recommended pharmacological interventions for BD during the peripartum period. It compares recent international treatment guidelines for the management of BD during the peripartum period. Last, this review presents a summary of key recommendations for BD women of childbearing age, for BD women during pregnancy and postpartum period from the international guidelines. Expert opinion : Management of the pharmacological treatment for BD patients during the perinatal period is challenging. Although treatment guidelines may be of significant help, high heterogeneity exists across them. Shared decision-making represents a useful patient-centered approach during the perinatal period. Large cohort studies are needed to better identify risk associated to treatment discontinuation or treatment exposure.